2016
DOI: 10.4314/thrb.v19i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of XpertMTB/Rif performance for diagnosis of tuberculosis among HIV positive patients in northern Tanzania

Abstract: Background: Diagnosis of tuberculosis (TB) in patients co-infected with HIV poses an important challenge because of the low sensitivity and specificity of microscopy, the standard diagnostic method. This study aimed to evaluate the performance of the XpertMTB/RIF tool for TB diagnosis among TB-HIV co-infected patients. Methods: This was a cross-sectional analytical study conducted at Kibong'oto Infectious Disease Hospital in northern Tanzania and involved 69 patients. The performance of the XpertMTB/RIF and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
0
6
0
10
Order By: Relevance
“…We considered five studies (6%) to have high risk of bias because the results of the reference standard were not blinded ( Chaisson 2014 ; Hanif 2011 ; Safianowska 2012 ; Zeka 2011 ; Zmak 2013 ) and the remaining 12 studies (14%) to have unclear risk of bias because information about blinding was not reported. With respect to applicability (Reference Standard domain), we considered most studies to have low concern; we considered one study to have high concern because this study did not speciate mycobacteria isolated in culture ( Mollel 2017 ) and two studies (2%) to have unclear concern because we could not tell ( Adelman 2015 ; Barmankulova 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We considered five studies (6%) to have high risk of bias because the results of the reference standard were not blinded ( Chaisson 2014 ; Hanif 2011 ; Safianowska 2012 ; Zeka 2011 ; Zmak 2013 ) and the remaining 12 studies (14%) to have unclear risk of bias because information about blinding was not reported. With respect to applicability (Reference Standard domain), we considered most studies to have low concern; we considered one study to have high concern because this study did not speciate mycobacteria isolated in culture ( Mollel 2017 ) and two studies (2%) to have unclear concern because we could not tell ( Adelman 2015 ; Barmankulova 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we considered 15 studies (17%) to have unclear risk of bias because the manner of participant selection was not stated (Atwebembeire 2016; Barmankulova 2015; Bates 2013a; Boum 2016; Chen 2017; Huang 2015; Kim CH 2015; Luetkemeyer 2016; Mbelele 2017; Moussa 2016; Mutingwende 2015; Nosova 2013a; Reechaipichitkul 2017; Shao 2017; Shenai 2016). With respect to applicability, we considered 46 studies (53%) to have low concern because participants in these studies were evaluated in primary care facilities, local hospitals, or both settings (Adelman 2015; Al‐Darraji 2013; Balcells 2012; Balcha 2014; Barmankulova 2015; Bjerrum 2016; Boehme 2010; Boehme 2011; Boum 2016; Calligaro 2017; Carriquiry 2012; Chen 2017; Dorman 2018; Friedrich 2011; Hanrahan 2013; Hanrahan 2014; Henostroza 2016; Huang 2015; Kurbaniyazova 2017; Kurbatova 2013; Kwak 2013; LaCourse 2016; Lawn 2011; Luetkemeyer 2016; Meawed 2016; Metcalfe 2015; Mollel 2017; Moure 2011; Mutingwende 2015; Ngabonziza 2016; Nliwasa 2016; O'Donnell 2015; Pimkina 2015; Reddy 2017; Rice 2017; Scott 2011; Scott 2017; Shao 2017; Shenai 2016; Sohn 2014; Ssengooba 2014; …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dos 19 artigos incluídos nessa revisão, 18 (94,7%) foram publicados em língua inglesa 6,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] e um (5,3%) em língua espanhola 39 , dos quais 15 (78,9%) são procedentes do Continente Africano 6,22,23,[25][26][27][28][29][30][31][32][33][34]36,38 , dois (10,5%), do Continente Americano 37,39 , um (5,3%), do Continente Asiático 24 e um (5,3%) estudo multicêntrico 35 envolve países da África, América, Europa e Ásia.…”
Section: Resultsunclassified
“…The commonly applied protocol for detecting MTB in Xpert at our hospital and in most other settings is the use of raw sputum to Xpert sample reagent (SR) with a ratio of 1:2 [ 10 , 12 ]. The SR contains 2% of sodium hydroxide (NaoH) and isopropanol.…”
Section: Introductionmentioning
confidence: 99%